Animosity. Volume 2, The dragon - Bennett, Marguerite; Bennett, Marguerite (Aftershock Comics, LLC, 2017)
"The world is plunged into chaos as the newly-intelligent Animals fight humanity, and simply fight each other, for their own life, liberty, and pursuit of happiness. in the midst of the turmoil is Jesse, an 11-year-old girl, and her dog, Sandor, who is devoted to Jesse and her protection. One year after the incident, Jesse and Sandor continue their cross-country journey to find Jesse's half-brother Adam in San Francisco...but they are unprepared for the various dangers that block their path."--Page 4 of cover